The design of the guest application system must report in RT 03 RW 04 appears website-based with the extreme programing method - Angga Suryadi; Intan Kumalasari (SEAN Institute, 2024)
RT stands for “Rukun Tetangga” which is led by a “Ketua RT”. The head of a RT is an individual elected by residents in a residential area, who has the responsibility to lead and manage activities and daily affairs within the RT area. RT areas have regulations that have long been implemented, namely guests who are not local residents have an obligation to report to the RT office within 1 x 24 hours during their visit to enter an area. This is done to provide a sense of security and order in the surrounding environment. However, these regulations often do not work as they should. So, to facilitate practice, research to design and build a web-based mandatory reporting guest application system was carried out. This website is designed to make it easier for guests to report when entering the RT.03 area without having to go to the RT head's office. The Extreme Programming (XP) method is used in making this website because the software development method is fast, efficient, low risk, flexible, predictable, scientific, and fun. The stages that need to be followed in building a mandatory guest reporting system with the XP method are planning, designing, coding, and system testing. From the results of this study, it can be concluded that the mandatory guest reporting system is very effective in helping to facilitate the guest labor process and also the data collection of guests who come.